What to do with minimal residual disease testing in myeloma - Manasanch, Elisabet E. (Hematology Am Soc Hematol Educ Program, 2019)
The role and use of minimal residual disease (MRD) testing has changed significantly over the past few years as it has become part of the routine care for response assessment in multiple myeloma. The most widely used standardized methods to assess MRD in myeloma in the bone marrow are multicolor flow cytometry and next-generation sequencing. Importantly, the depth of MRD negativity in the bone marrow correlates with improved progression-free survival and overall survival in myeloma. Whole-body position emission tomography–computed tomography and magnetic resonance imaging are also used to evaluate patchy and extramedullary disease, which may not be readily visible through bone marrow assessment. This article reviews a clinical case in which MRD testing, both in bone marrow and in functional imaging, is part of the standard of care. It also reviews the different modalities of MRD testing and current practice guidelines. Finally, patients with myeloma may be tested for MRD after treatment because this is part of the routine response assessment according to International Myeloma Working Group criteria and correlates with clinical outcomes. Important questions such as when to stop therapy for sustained MRD-negative patients or whether to change treatments for patients who go from MRD negative to positive without other evidence of disease relapse are being evaluated in clinical trials and remain controversial.